The Need to Change the Doctor - Patient Communication Model in Contemporary Medical Practice - Shopnikolova, PhD, Dr. Tsvetelina (International Journal of Innovative Research in Medical Science, 2025)
Communication between doctor and patient is a key factor for the effectiveness of the diagnostic–therapeutic process and achieving sustainable health outcomes. Despite technological advances and increasingly sophisticated treatments, insufficient information exchange and mutual understanding can compromise the quality of medical care. This article examines the necessity of transitioning from the traditional, hierarchical, often one-way communication model to a modern, bidirectional, partnership-based approach founded on empathy, active listening, and shared decision-making. The methodology includes a systematic review of scientific literature and a comparative analysis of existing communication models. The results indicate that improving communication leads to higher patient satisfaction, better adherence to treatment regimens, a reduction in medical errors, and optimized resource use, particularly in terms of time efficiency and more effective allocation of healthcare personnel. The conclusion is that transforming the communication model is imperative for modern healthcare, especially in the context of digitalization and rising health literacy.